1996
DOI: 10.1002/j.1460-2075.1996.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein dimerization between Lmo2 (Rbtn2) and Tal1 alters thymocyte development and potentiates T cell tumorigenesis in transgenic mice.

Abstract: The LMO2 and TAL1 genes were first identified via chromosomal translocations and later found to encode proteins that interact during normal erythroid development. Some T cell leukaemia patients have chromosomal abnormalities involving both genes, implying that LMO2 and TAL1 act synergistically to promote tumorigenesis after their inappropriate co‐expression. To test this hypothesis, transgenic mice were made which co‐express Lmo2 and Tal1 genes in T cells. Dimers of Lmo2 and Tal1 proteins were formed in thymoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
204
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(210 citation statements)
references
References 35 publications
5
204
1
Order By: Relevance
“…LMO1 and LMO2 contain tandem copies of a protein interaction motif termed the LIM domain and have each been shown to cooperate with TAL1 in inducing thymic neoplasms in bitransgenic mice (Aplan et al, 1997;Larson et al, 1996). LMO2 has also been identi®ed in DNA-binding complexes in erythroid cells containing TAL1, the zinc ®nger transcription factor GATA-1, and the LIM domain-binding protein Ldb1/NL1 (Wadman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMO1 and LMO2 contain tandem copies of a protein interaction motif termed the LIM domain and have each been shown to cooperate with TAL1 in inducing thymic neoplasms in bitransgenic mice (Aplan et al, 1997;Larson et al, 1996). LMO2 has also been identi®ed in DNA-binding complexes in erythroid cells containing TAL1, the zinc ®nger transcription factor GATA-1, and the LIM domain-binding protein Ldb1/NL1 (Wadman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…While this issue cannot be resolved until its target genes are identi®ed, the observation that p300 augmented transcription by Tal1 coding sequences corresponding to its two principal protein products, at least in the context of GAL4-Tal1 fusion proteins, may have relevance to their respective actions. Although both isoforms were found to cooperate with LMO1 or LMO2 in inducing T-cell leukemia in transgenic mice (Aplan et al, 1997;Larson et al, 1996), it was suggested that by virtue of lacking an activation domain, pp24 TAL1 did so as a transdominant negative inhibitor (Aplan et al, 1997). In contrast, our results predict that both TAL1 gene products could act in association with p300 as positive transcriptional regulators, and, indeed, pp24 TAL1 and pp47 TAL1 were similarly e ective at transactivating a reporter gene with LMO1 and LMO2 (Ono et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…One possible somatic event may be the inappropriate expression or loss of scl-binding partners. For example, the CD2-scl transgene accelerates lymphomagenesis in LMO-2 transgenic mice, presumably by increasing the number of scl-LMO-2 heterodimers (Larson et al, 1996). Also, lymphomagenesis in lckscl mice is enhanced by the co-expression of a case in kinase IIa transgene (Kelliher et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this speci®c association with T-ALL, experimental evidence that scl is oncogenic has, until recently been relatively scant. Although there was evidence that scl could function as an oncogene in a v-abl transformed murine cell line , transgenic mice carrying scl coupled to the human T-lymphoid speci®c CD2 enhancer (CD2-scl) did not develop T-cell malignancies despite high levels of scl expression in their thymocytes (Robb et al, 1995b;Larson et al, 1996). Recently, a role for scl in leukemogenesis was con®rmed by two groups who showed that animals carrying an scl transgene driven by the proximal lck promoter develop thymic T-cell lymphomas (Condorelli et al, 1996;Kelliher et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…insulin) or direct cellular differentiation in cooperation with other nuclear factors (Perez-Alvarado et al, 1994). Other examples include, E47/Pan-1 and Lmx1.1 transcription factors, which have been shown to interact with LMO2, a LIM only protein, and with TAL1, LYL1, and LYL2 to regulate gene activation (Sadler et al, 1992;Warren et al, 1994;Larson et al, 1996;Johnson et al, 1997;Dawid et al, 1998). Similarly, the rat cysteine-rich intestinal protein (CRIP), the human cysteine-rich protein (CRP), and rhombotin-1 and -2 have been implicated as protein crosslinkers in transcription regulation (Dawid et al, 1998).…”
Section: Discussionmentioning
confidence: 99%